Generation of low repetition rate sub-nanosecond pulses in doubly QML Nd:Lu0.5Y0.5VO4 and Nd:YVO4 lasers with EO and transmission SSA. (June 2015) - Zhang, Haijuan; Zhao, Shengzhi; Zhao, Jia; Yang, Kejian; Li, Guiqiu; Li, Dechun; Li, Tao; Qiao, Wenchao; Wang, Yonggang
Abstract: By employing the mixed crystal Nd:Lu0.5 Y0.5 VO4 and the single crystal Nd:YVO4 as the laser media, the characteristics of the QML laser doubly modulated by electro-optic (EO) modulator and transmission semiconductor saturable absorber (T-SSA) are studied. Under the same cavity parameters, the properties of the low repetition rate sub-nanosecond pulses generated from Nd:Lu0.5 Y0.5 VO4 and Nd:YVO4 laser are compared. The experimental results show that Nd:Lu0.5 Y0.5 VO4 laser can generate shorter pulse width than Nd:YVO4 laser, and meanwhile, needs lower pump power to generate low repetition rate sub-nanosecond pulses. The shortest pulse durations obtained from the doubly QML Nd:Lu0.5 Y0.5 VO4 and Nd:YVO4 lasers are estimated to be 204 and 294 ps, with the corresponding peak power of 3.4 and 3.04 MW, respectively. Highlights: Doubly QML laser with EO modulator/semiconductor saturable absorber is realized. Properties of Nd:Lu0.5 Y0.5 VO4 and Nd:YVO4 crystals are comparatively studied. Nd:Lu0.5 Y0.5 VO4 can generate shorter Q-switched envelope and mode-locking pulse. Nd:Lu0.5 Y0.5 VO4 can produce low repetition rate sub-ns pulses at lower pump power.